Modulating oxidative stress and neurogenic inflammation: the role of topiramate in migraine treatment - Qiao-Wen Chen; Qiao-Wen Chen; Run-Tian Meng; Run-Tian Meng; Chih-Yuan Ko (Frontiers in Aging Neuroscience, 2024)
Migraine is a chronic, recurrent neurovascular disorder characterized by episodes closely associated with neurovascular hypersensitivity. Oxidative stress can worsen the hypersensitive state of the central nervous system, which in turn can trigger pro-inflammatory factors that result in neurogenic inflammation. Topiramate is frequently used as a preventative measure for migraines, but there is currently little empirical data to support its efficacy through pathways related to neurogenic inflammation and oxidative stress. This review provides an overview of current knowledge regarding the etiology, inducements, pathophysiology, and available treatments for migraine, with a focus on the clinical and experimental evidence of neurogenic inflammation and oxidative stress in migraine. It also delves into the antioxidant and anti-inflammatory qualities of topiramate, clarifying the possible ways in which topiramate affects these pathways to lessen migraine symptoms.